2021
DOI: 10.7343/as-2021-537
|View full text |Cite
|
Sign up to set email alerts
|

Studies on water resources salinization along the Italian coast: 30 years of work

Abstract: The population density on the Italian coasts is twice the national average. Numerous urban, economic, and productive settlements lie along the coast, which in many areas have altered the natural characteristics of the territory. Moreover, recent climate change studies forecast large impacts on the hydrologic cycle in the Mediterranean. Thus, in the next years, coastal water resources will be gradually more stressed. This in turn may result in a progressive salinization, which is a widespread and worrying pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Fresh groundwater resources in coastal aquifers are significantly impacted by seawater intrusion (Chang & Yeh, 2010;Mastrocicco, 2021). Climate change, sea level rise, change in land use and excessive groundwater pumping led to severe seawater intrusion (Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Fresh groundwater resources in coastal aquifers are significantly impacted by seawater intrusion (Chang & Yeh, 2010;Mastrocicco, 2021). Climate change, sea level rise, change in land use and excessive groundwater pumping led to severe seawater intrusion (Yang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The mixing zone separating freshwater and seawater influences the depth at which freshwater is available [9]. Usually, in small islands' subsoil, the mixing zone contains a gradual transition in salinity from freshwater to seawater as well [6,10,11], and its thickness is related to the tidal fluctuations [12,13]. Buddemeier and Oberdorfer [14] suggested that the mixing zone, defined by salinities between 2.5% and 95% of seawater concentration, can occupy a significant volume of atoll island aquifers compared to the freshwater component.…”
Section: Introductionmentioning
confidence: 99%